2021
DOI: 10.3892/or.2021.8120
|View full text |Cite
|
Sign up to set email alerts
|

Egr‑1 inhibits colon cancer cell proliferation, migration and invasion via regulating CDKL1 at the transcriptional level

Abstract: Colon cancer is one of the most common malignant tumors worldwide, and the molecular mechanisms involved in the oncogenesis and progression of colon cancer remain unclear. Early growth response 1 (Egr-1) is a transcription factor that is closely associated with several tumor processes; however, its role in colon cancer is unknown. The present study aimed to explore the function and mechanism of transcription factor Egr-1 in colon cancer progression. The association between Egr-1 expression and the survival of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…EGR1 has been considered as a therapeutic target for multiple diseases, such as prostate cancer, lymphoid tumors, Alzheimer's disease, and diabetes [ 10 13 ]. EGR1 plays a vital role in many biological programs, including cell survival, cell death, apoptosis, cell motility, and metastasis [ 9 , 14 , 15 ]. EGR1 is demonstrated to have a critical role in angiogenesis as well.…”
Section: Introductionmentioning
confidence: 99%
“…EGR1 has been considered as a therapeutic target for multiple diseases, such as prostate cancer, lymphoid tumors, Alzheimer's disease, and diabetes [ 10 13 ]. EGR1 plays a vital role in many biological programs, including cell survival, cell death, apoptosis, cell motility, and metastasis [ 9 , 14 , 15 ]. EGR1 is demonstrated to have a critical role in angiogenesis as well.…”
Section: Introductionmentioning
confidence: 99%
“…Early growth response-1 (EGR1) is a transcription factor involved in cell proliferation and in the regulation of apoptosis. Several previous studies showed that EGR1 exhibits prominent tumor suppressor function in glioma (44), non-smallcell lung cancer (45), colon cancer (46), papillary thyroid carcinoma (47), and breast cancer (48). Saha et al indicated that low levels of EGR1 expression were positively correlated with poor survival for RFS and distant metastasis-free survival (DMFS) in breast cancer (49).…”
Section: Discussionmentioning
confidence: 99%
“…The Egr-1 gene, as a member of the zinc finger structure transcription factor family, is located on human chromosome 5q31 and encodes a DNA-binding transcription factor of ~80 kDa (39). It has been demonstrated that Egr-1 serves an important role in cell growth, differentiation and apoptosis (16,(40)(41)(42)(43)(44). At the same time, Egr-1 is closely associated with the occurrence and development of certain diseases, for example tutor and leukemia, however the specific signaling pathway of each of them remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…It is the superiority of the aforementioned induced differentiation therapy that has made differentiation induction a research hotspot in recent years (12)(13)(14)(15). Expression of early growth response-1 (Egr-1) is a member of the early growth response protein family, which has been considered to be of great significance in a variety of physiological processes and has been extensively studied (16,17), especially in cell proliferation, angiogenesis, invasion and immune response of tumors (18,19). Egr-1 can act as a transcriptional regulator by combining the C2H2 type zinc finger with the DNA motif of the 5'-GCG(T/G)GGGCG-3' sequence.…”
Section: Mir-let-7c-3p Targeting On Egr-1 Contributes To the Committe...mentioning
confidence: 99%
See 1 more Smart Citation